The controlling the hydraulic electro drive system on the basis of the adaptive sliding mode control method - Tran Duc Chuyen; Nguyen Thanh Tien; Vu Duy Hung; Pham Ngoc Sam; Tran Hai Duong (Institute of Advanced Engineering and Science, 2023)
In this paper, presents the construction of an automatic control system for mobile lifting machines applied in industry and traffic. The control algorithm is built on the basis of calculations from the actual system taking into account the estimation of the nonlinear factors of frictional moment uncertainty, on the basis of the adaptive sliding mode control method. Using programming and simulation tools on the basis of MATLAB/Simulink to demonstrate the research results. The results of the simulation study are the basis for the design and calculation of the hydraulic electro drive system, which shows the practical effectiveness of the study of electromechanical traction electric transmission systems such as mobile lifting machines. The motion uses hydraulic valve systems to transmit power control (lifting and lowering as required).